International News Agencies Treatment of the Great Return Marches A Case Study of Agence France Presse “AFP” - Hussein AL -Turk, Ahmad Oraby Hussein AL -Turk (ALBAHITH ALALAMI, 2018)
This study examines Agence France Presse’s (AFP) media treatment of the Great Return Marches in order to identify its contents, the issues it gave attention to, its sources, attitude, techniques, objectives, the journalistic forms used in covering events and the typographic elements used to highlight them.This descriptive study employed the survey methodology through the use of content analysis method, and the methodology of mutual relations through the use of the case study method. The data was collected by means of a content analysis form. The study was based on the Agenda Setting Theory in the analysis of the study results. The study sample included (116) news texts from AFP collected during the period from 20/3/2018 to 15/9/2018 using the comprehensive survey method.The study reached a number of results, the most important of which are that the topic of the martyrs of the Return Marches ranked first at (20.6%), while the topic of the participation of women and the elderly and ‘arrests topics’ did not receive considerable attention at (0.6%). The Palestinian official sources ranked first by (22.8%), while the category of no source came in the lead in press sources at (78.4%). The objective of holding the “Israelis” the responsibility was at the forefront of the objectives that the Agency seeks to achieve at (23.6%). The news story ranked first at (60.3%) followed by the press article at (31.9%).